Si/ZnO:Coumarin photocapacitor for electro and photonic applications - Yalcin, Mesut; Dere, Aysegul; Yakuphanoğlu, Fahrettin (Elsevier, 2024)
The present study first investigated the photocapacitance measurements of Al/p-Si/ZnO:Coumarin/Au metal-oxide-semiconductor MOS device at room temperature in the frequency range of 10 kHz-1MHz and bias voltage range of 5 V; +5 V. Based on photocapacitance analysis, V-bi, N-a, N-ss, E-f, E-m, Delta phi(b), phi(b), W-d values were calculated for 10 kHz, 100 kHz and 1 MHz. For 1 MHz, V-bi value was 0.79 eV, N-a value was 3.54x10(15) cm(-3), phi(b) value was 0.99 eV and W-d value was 530 nm. Additionally, the dielectric constant (epsilon'), dielectric loss (epsilon '''), electrical modulus (M'M '') and complex impedance (Z*), tangent loss (tan delta), ac conductivity(sigma(ac)) and phase angle (phi) values of the device were also calculated. epsilon' values were calculated 116 at 10 kHz, 58 at 100 kHz and 6 at 1 MHz. These epsilon' values indicate that the higher ZnO:Coumarin layer can store more charge carriers. This study has shown that materials produced by ZnO, a metal oxide semiconductor, doped with coumarin have the potential to be used in many optoelectronic devices, especially in photonic applications.
Keywords: Coumarin; Dielectric constant; Dielectric loss; Complex impedance; Alternative current (ac) conductivity